Judgment of horizontal well liquid loading in fractured low-permeability gas reservoirs. (18th June 2022) - Zhang, Hongtao; Guo, Tianyue; Zhang, Yongping; Wang, Fengshan; Fu, Cheng; Zhu, Tingting; Huang, Bin; Li, Qingyuan
Abstract: In order to solve the problem that the wellbore liquid loading of low permeability horizontal wells can't be predicted accurately in previous studies, this article establishes a new matrix - natural fracture - wellbore horizontal gas well productivity equation considering stress sensitivity, starting pressure gradient and high speed turbulence effect. The method is used to judge whether there is liquid loading in a gas reservoir, and verified by the critical liquid carrying flow method. The results show that the accuracy rate of predicting liquid loading by productivity equation method is 80%, and the accuracy rate of predicting gas well productivity is 91.55%. Meanwhile, the influence rule of natural fracture parameters on productivity is given and it is found that the stress sensitivity coefficient has little effect on productivity. At the same bottom hole pressure, the gas production gradually decreases with the increase of high-speed nonlinear coefficient and gas production gradually increases with the increase of the number and width of natural fractures. The findings of this study can help for better understanding of the relationship between wellbore liquid loading and gas well productivity, and then better grasping the timing of gas well drainage and gas recovery.